RENTABILITAS PT INDOFOOD SUKSES MAKMUR Tbk MERUPAKAN DAMPAK DARI NILAI LEVERAGE, KEBIJAKAN DIVIDEN DAN PERPUTARAN MODAL KERJA - Anik Susilowati (FEB Universitas Maritim Semarang, 2022)
This study aims to determine the effect arising from Leverage, Dividend Policy and Working Capital Turnover in the company PT Indofood Sukses Makmur Tbk for the period 2012-2021. This study uses secondary data with a sample of 40 from the quarterly financial statements for 10 years belonging to PT Indofood Sukses Makmur Tbk. The data was obtained from the Indonesia Stock Exchange (IDX) website. The data that has been collected then goes through a prerequisite test, namely the Classic Assumption Test, Validity Test and Reliability Test before testing the hypothesis (multiple linear regression). The conclusion from the results of this study is that partially Leverage has a significant negative effect on company profitability. Dividend Policy Variable partially has a significant negative effect on the company's profitability. Partially, the Working Capital Turnover variable has no significant negative effect on the company's profitability. Leverage, Dividend Policy, and Working Capital simultaneously have a significant positive effect on the company's profitability, while the results of the coefficient of determination with a value of 0.726 which means that Leverage, Dividend Policy and Working Capital have an effect of 72.6% on the Company's Profitability and the remaining 27.4% influenced by other variables not included in this study.